2016
DOI: 10.2320/matertrans.m2016084
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Zn–Zr Oxide Composite from Dispersed-Particle-Free Solution

Abstract: Electrodeposition of Zn-Zr oxide composite from an unagitated sulfate solution containing Zn 2+ and Zr ions was investigated at pH 1-2 and at 313 K under galvanostatic conditions. The Zr content was higher in deposits formed from the solution at pH 2 than in those formed from the solution at pH 1 and initially decreased with increasing current density; however, when the current density was increased further, the Zr content in the deposits increased. This increase in Zr content was attributed to the accelerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…27) The pH titration curves of the ZnZr and ZnV solutions have been investigated and it was reported that the Zr 4+ ions are hydrolyzed at low pH. 19,20,22,23) That is, ZrO 2 •H 2 O is more readily formed than V 2 O 4 at the cathode layer during deposition. Nevertheless, the current efficiency for Zn deposition was lower in the presence of VO 2+ (Fig.…”
Section: Effect Of Peg Addition On the Deposition Behavior Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…27) The pH titration curves of the ZnZr and ZnV solutions have been investigated and it was reported that the Zr 4+ ions are hydrolyzed at low pH. 19,20,22,23) That is, ZrO 2 •H 2 O is more readily formed than V 2 O 4 at the cathode layer during deposition. Nevertheless, the current efficiency for Zn deposition was lower in the presence of VO 2+ (Fig.…”
Section: Effect Of Peg Addition On the Deposition Behavior Ofmentioning
confidence: 99%
“…Al 3+ , Zr 4+ , and VO 2+ ions, which hydrolyze at low pH, can be added into a Zn electrolyte solution, and their metal oxides co-deposit with Zn. 1826) However, Al 3+ and Zr 4+ ions rarely co-deposit with Zn as an oxide, 20,23,24) whereas VO 2+ ions co-deposit with Zn as an oxide, but the dispersion of fine particles in the deposited Zn is nonuniform. 18,19,21,22) Therefore, in this study, Zr 4+ and VO 2+ ions were added into Zn electrolyte solution, wherein PEG was used as an additive to promote the hydrolysis reaction.…”
Section: Introductionmentioning
confidence: 99%
“…18,19) Therefore, when metal ions (M n + ) that hydrolyze at low pHs are added to electrolyte solutions as a second element, they turn into solid hydroxides or oxides via a hydrolysis reaction (M n + +nH 2 O→M(OH) n + nH + ) and codeposit with the deposited Zn films. [20][21][22][23][24][25][26][27][28][29][30] Thus, the hydrolysis reaction during electrodeposition facilitates composite electrodeposition, without the need for the addition of insoluble solid particles into the electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…However, Zn films with Zr hydroxide or oxide dispersed uniformly on the surface were not obtained. [25][26][27][28][29][30] This was attributed to the hydrolysis reaction of ZrO 2 + ions (ZrO 2 + + 3H 2 O → Zr(OH) 4 + 2H + or ZrO 2 + + H 2 O → ZrO 2 + 2H + ) proceeding partially on the Zn surface under electrolysis at a constant current density. If the hydrolysis reaction of ZrO 2 + ions occurs at the site of the hydrogen evolution reaction, the hydrolysis reaction of ZrO 2 + ions should proceed uniformly when the hydrogen evolution reaction occurs uniformly.…”
Section: Introductionmentioning
confidence: 99%
“…1723) The results of these studies show that Al 3+ and Zr 4+ ions rarely codeposit with deposited Zn as their hydroxides and oxides. 19,22,23) In this study, Zr 4+ ions were added into electrolyte, and the effect of additives to raise pH at cathode layer during Zn deposition was investigated to accelerate the hydrolysis reaction of Zr 4+ ions. Nitrate ions (NO 3 ¹ ) and polyethylene glycol (PEG) were selected as additives.…”
Section: Introductionmentioning
confidence: 99%